Tag and recapture of European hake (Merluccius merluccius L.) off the Northwest Iberian Peninsula: First results support fast growth hypothesis - Piñeiro-Álvarez, Carmen Gloria; Rey-Sanz, Javier; Pontual, Hélène de; Goñi, Raquel (Fisheries Research, 2007)
Este es un artículo aceptado para publicación en Fisheries Research siguiendo revisión por pares. La versión definitiva puede consultarse en la web del editor. In the first tagging experiment of European hake (Merluccius merluccius L.) conducted off the NW Iberian Peninsula to study hake growth in the wild we released 527 live tagged individuals. The survival rate after capture and tagging was 58%. Mortality during capture was positively correlated with depth of capture and negatively correlated with hake size. Fifteen months after tagging, seven individuals (1.3%) had been recaptured with times at liberty ranging from 29 to 466 days. We provide the first direct measurements of growth rates of Southern stock European hake in the wild and compare them with rates obtained from tagging experiments in other regions and with rates derived from conventional otolith age reading. The mean somatic growth rate of all recaptured hake was 0.032 ± 0.016 cm day−1 (sexes combined), while the mean growth rate of the two hake with over 340 days at liberty was 0.052 ± 0.003 cm day−1 (sexes unknown). These results indicate that conventional otolith age reading methods overestimate age and underestimate growth. peer reviewed